2023
DOI: 10.3390/ani13071186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Saccharomyces cerevisiae Postbiotic Feed Additive on Salmonella Enteritidis Colonization of Cecal and Ovarian Tissues in Directly Challenged and Horizontally Exposed Layer Pullets

Abstract: Determining the efficacy of feed-additive technologies utilized as pre-harvest food-safety interventions against Salmonella enterica may be influenced by factors including, but not limited to, mechanism of action, experimental design variables, Salmonella serovar(s), exposure dose, route, or duration in both controlled research and real-world field observations. The purpose of this study was to evaluate the dietary inclusion of a Saccharomyces cerevisiae fermentation-derived postbiotic (SCFP) additive (Diamond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In addition to the ileum and cloaca, cecal pouches are the preferred organs for SE colonization and establishment after it is ingested by chickens [35]. After an SE challenge, SE colonized the ceca of young layer pullets [21,26,29,30,36], layer pullets near sexual maturity [24,25,27,28], and adult laying hens [21][22][23]. In this study, orally infecting layer pullets with an SE dose of 6.3 × 10 7 CFU at 8 days of age resulted in colonization of the ceca, as evidenced by load and prevalence of SE in the ceca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the ileum and cloaca, cecal pouches are the preferred organs for SE colonization and establishment after it is ingested by chickens [35]. After an SE challenge, SE colonized the ceca of young layer pullets [21,26,29,30,36], layer pullets near sexual maturity [24,25,27,28], and adult laying hens [21][22][23]. In this study, orally infecting layer pullets with an SE dose of 6.3 × 10 7 CFU at 8 days of age resulted in colonization of the ceca, as evidenced by load and prevalence of SE in the ceca.…”
Section: Discussionmentioning
confidence: 99%
“…Mannan oligosaccharides (MOSs), fructo-oligosaccharides (FOSs), and galacto-oligosaccharides (GOSs) are among the more commonly employed prebiotics in animal and poultry research [17], and other new prebiotic technologies, such as mannabiose (MNB), which are derivatives of MOS, have been shown to be efficacious for use in controlling SE in poultry [20]. Bacillus probiotics [21][22][23] and MOS prebiotics [23][24][25][26][27] have been shown to reduce SE colonization in layer birds. In addition, Bacillus-based probiotics and yeast cell wall-based prebiotics are among the most used feed additives in poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Choe et al reported that supplementing layer birds with soluble metabolite combinations of L. plantarum strains improved egg production performance, fecal population of LAB, and intestinal villi height and crypt depth [157]. Additionally, postbiotics derived from Saccharomyces cerevisiae fermentation reduced the cecal colonization of Salmonella in broilers and layer pullets, making them a potential preharvest intervention to enhance food safety and improve production performance [158,159].…”
Section: Postbioticsmentioning
confidence: 99%